Enhancing the Li-ion storage performance of graphite anode material modified by LiAlO2. (1st May 2017) - Wu, Yan; Li, Yi-Fan; Wang, Li-Ying; Bai, Yu-Jun; Zhao, Zhen-Yang; Yin, Long-Wei; Li, Hui
Abstract: As a promising lithium-conducting solid electrolyte, LiAlO2 has not gained deserved attention in the modification of lithium ion batteries anode material. In this paper, the LiAlO2 /C nano-composites have been prepared by simply mixing with the appropriate proportion of Al(NO3 )3, LiNO3 and graphite homogeneously and subsequent sintering. The successfully prepared LiAlO2 nano-particles are investigated by X-ray photoelectron spectra (XPS) and X-ray diffraction (XRD). The electrochemical tests indicate that the LiAlO2 /C composite exhibits outstanding circulation property at a current density of 0.1C and excellent rate performance. Both the Scanning Electron Microscope (SEM) test and the Raman spectra shows that sintering induces the increase of the disordered degree of the surface and the uniform distribution of the LiAlO2 nano-particles, both of which are valuable for improvement of the battery performance. First-principles calculations are used to confirm the transfer pathway of the Li-ion which indicates a possibility of using inorganic compounds to improve the electrochemical performance of graphite. It is concluded that Li-ion can pass through the lattice via vacancies and the interstitial Li in the lattice.